PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA MELALUI STRES KERJA KARYAWAN DELTA SUPER STORE KRAKSAAN - Nora, Elfia; JudatusShidqiyah, Asih (IQTISHODUNA, 2015)
This research was conducted in DELTA Super Store Kraksaan at the beginning and the end ofAugust 2010. The subject of this research is part of the sale employee (salesman and salesgirl) of DELTASuper Store Kraksaan that consists of 100 people. Meanwhile the sample was taken as many as 80 people withthe sampling technique using simple random sampling. Data analysis that is used is a path analysis, an appliedform of multiple regression analysis, and the purpose is to know the direct or indirect effect of independentvariable on the dependent variable through intervening variable in a research. The result of this researchindicates that physical work environment (X1) has no significant effect on the employee work stress (Z) inDELTA Super Store Kraksaan with a significance, as well as non physical work environment (X2) also has nosignificant effect on the work stress (Z) with a significance, while physical work environment (X1) has significanteffect on the work motivation (Y), non physical work environment (X2) has significant effect on the workmotivation (Y), and work stress (Z) has significant negative effect on work motivation (Y), suggested thatDELTA Super Store Kraksaan must be more pay attention to what any factors can effect employee workmotivation, such as work environment condition both physical or non physical that can make the employeemore enthusiastic in working.